Making a world after empire : the Bandung moment and its political afterlives - Lee, Christopher J. (Ohio University Press, 2019)
In April 1955, twenty-nine countries from Africa, Asia, and the Middle East came together for a diplomatic conference in Bandung, Indonesia, intending to define the direction of the postcolonial world.